PENGARUH GREEN MARKETING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KEPUTUSAN KONSUMEN MEMBELI PRODUK AIR MINUM DALAM KEMASAN AQUA (Pada Mahasiswa Fakultas Ekonomi Universitas Baiturrahmah Padang) - Afrida, Afrida; Febriani, Rina (Eko dan Bisnis: Riau Economic and Business Review, 2021)
The success of a company in influencing consumers in purchasing decisions is strongly supported through a healthy lifestyle for consumers. So the company must determine the right marketing strategy to survive and handle competition.Â  The purpose of this study was to determine the factors that influence consumer decisions to buy bottled drinking water for students of the Faculty of Economics, University of Baiturrahmah Padang. The research method used is descriptive quantitative method. The population in this study were students of the Faculty of Economics, University of Baiturrahmah Padang who made purchasing decisions for bottled drinking water of Aqua. The sample in this study were 247 respondents. The data analysis technique in this study is multiple linear regression consisting of a partial test (t test), simultaneous test (f test), and determinant coefficient (R-Square).The results of this study indicate that green marketing partially has a significant positive effect on the decision to purchase bottled drinking water for the students of the Faculty of Economics, University of Baiturrahmah Padang. Meanwhile, partially coporate social responsibility has no significant positive effect on the decision to purchase bottled drinking water for Aqua students at the Faculty of Economics, University of Baiturrahmah Padang. Meanwhile, the simultaneous test shows that green marketing and corporate social responsibility have an effect together.